New data on the Opheliidae (Annelida) from Lizard Island (Great Barrier Reef, Australia): five new species of the genus Armandia Filippi, 1861 - Moreira, Juan; Parapar, Julio (Zootaxa, 2017)
The study of benthic samples collected in Lizard Island (Great Barrier Reef, Australia) has yielded five additional new species of the genus Armandia (Annelida, Opheliidae). Armandia buccina n. sp. is distinguished by the peculiar buccin-shape of the anal tube, A. casuarina n. sp. by having elongated prechaetal lobe in chaetigers 1–2 and one pair of basal anal papillae provided in turn with small papillae, A. mariacapae n. sp. by the elongated, triangular tip of the prechaetal lobe in all chaetigers, A. opisthoculata n. sp. by having two large pigmented spots at both sides of the unpaired anal cirrus, and A. parva n. sp. has a conspicuous short prostomium that is distally truncated. All species are described and illustrated, and an updated key to all Armandia species from South-East Asia and Australasia is also provided.